2021
DOI: 10.3389/fmolb.2021.648180
|View full text |Cite
|
Sign up to set email alerts
|

An Illustrated Guide to the Imaging Evolution of COVID in Non-Epidemic Areas of Southeast China

Abstract: Purpose: By analyzing the CT manifestations and evolution of COVID in non-epidemic areas of southeast China, analyzing the developmental abnormalities and accompanying signs in the early and late stages of the disease, providing imaging evidence for clinical diagnosis and identification, and assisting in judging disease progression and monitoring prognosis.Methods: This retrospective and multicenter study included 1,648 chest CT examinations from 693 patients with laboratory-confirmed COVID-19 infection from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Ground-glass opacity often appears as a radiological image of partial alveolar spaces filled with fluid or thickened interstitial lung. 18 A study by Wang et al (2021) found that GGO lesions can develop into consolidation. It usually takes 7 days for consolidation to occur, while it takes 15 days for consolidation to turn back into GGO.…”
Section: Chest X-ray Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground-glass opacity often appears as a radiological image of partial alveolar spaces filled with fluid or thickened interstitial lung. 18 A study by Wang et al (2021) found that GGO lesions can develop into consolidation. It usually takes 7 days for consolidation to occur, while it takes 15 days for consolidation to turn back into GGO.…”
Section: Chest X-ray Characteristicsmentioning
confidence: 99%
“…The distribution and location of lesions are not significantly associated with the time and duration of lesions. 20…”
Section: Chest X-ray Characteristicsmentioning
confidence: 99%